Research on Compliance and Cross-Border Transfer Technology of Customer Data in Financial CRM Systems - Qiu, Yanmin (Law and Economy, 2026)
In the context of the global data regulatory system reconstruction, customer data in financial CRM systems, characterized by sensitivity and cross-border mobility, face the core dilemma of “imbalance between compliance and transfer efficiency.” Based on the 2024 industry report by the International Financial Association and practical scenarios of multinational securities brokers, this paper proposes a three-dimensional technical framework of “dynamic grading – encryption adaptation – on-chain notarization” through literature research, model construction, and empirical testing. Using a sample of one million customer data records from a multinational securities broker, the results show that the framework achieves a compliance pass rate of 100%, reduces transfer latency from 189ms to 32ms (an improvement of 83%), lowers compliance audit labor costs by 42%, shortens the duration of cross-border business processing by 73%, and increases customer satisfaction by 27%. This study establishes a dynamic grading model for financial data across jurisdictions for the first time, filling the theoretical gap in balancing “compliance and efficiency.” The technical solution has been implemented in three multinational financial institutions, reducing compliance risk losses by over 20 million yuan annually, providing practical references for the data security governance of financial technology.